2009
DOI: 10.1111/j.1440-0960.2009.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczema workshops reduce severity of childhood atopic eczema

Abstract: An intervention study was conducted to assess the effectiveness of a nurse-led eczema workshop in reducing the severity of atopic eczema in infants, children and adolescents. Ninety-nine new patients referred to the Dermatology Department of The Royal Children's Hospital in Melbourne, Australia, for the management of atopic eczema were randomized to receive care from an eczema workshop or a dermatologist-led clinic. Patients were followed-up 4 weeks after the intervention. The primary outcome was the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 17 publications
4
123
0
3
Order By: Relevance
“…The nurse-led workshops in the study by Moore and colleagues 356 were found to confer a statistically significant decrease in eczema severity compared with the dermatologist consultations, with a mean difference in SCORAD score between the treatment groups of -9.93 (95% Cl -14.57 to -5.29; p < 0.001). It is not reported whether the SCORAD assessors were blinded but it is unlikely that this was the case.…”
Section: Benefitsmentioning
confidence: 86%
See 2 more Smart Citations
“…The nurse-led workshops in the study by Moore and colleagues 356 were found to confer a statistically significant decrease in eczema severity compared with the dermatologist consultations, with a mean difference in SCORAD score between the treatment groups of -9.93 (95% Cl -14.57 to -5.29; p < 0.001). It is not reported whether the SCORAD assessors were blinded but it is unlikely that this was the case.…”
Section: Benefitsmentioning
confidence: 86%
“…An Australian trial by Moore and colleagues 356 compared one 90-minute 'workshop' with a dermatology nurse consultant with an average 40-minute consultation with a dermatologist in 165 children with a new referral for eczema. The nurse-led workshop involved a history being taken and SCORAD scores being obtained, an examination, a management plan, a demonstration of techniques for applying treatments and prescriptions and equipment cards being obtained.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15 For these reasons, AD education that addresses the pathophysiology of the disease, its management, and practical demonstrations has the potential to improve clinical outcomes. 11,16 However, the interventions previously cited in the literature may be timeconsuming and costly in clinical practice, thereby potentially limiting their widespread implementation. In this study, we created educational online videos and written pamphlets for patients with AD that are readily accessible and distributable.…”
mentioning
confidence: 99%
“…Studies on demonstration of treatments by a specialist nurse have shown the benefi t of this [93][94][95][96] . Carroll et al [ 59 ] suggested that the cost of treating eczema could be reduced by 'targeting parents and caregivers with education and psychosocial support' that might decrease family and personal burden'.…”
Section: Factors Thought To Improve Treatment Adherencementioning
confidence: 99%